Risk factors for chronic diseases between participants of the program Living with Style and Health - Meimei Brevidelli, Maria (O Mundo da Saúde, 2017)
The growing prevalence of diabetes and hypertension is of concern to public health organizations, as well as healthcare workers. The prevention and control of these diseases is now a priority in primary health care, and public policies encourage the promotion of a healthy lifestyle. The objectives of the study were to describe the prevalence of risk factors for chronic diseases in a population of adults participating in a health program, and to investigate associations between genders. A cross-sectional study with 160 adult individuals enrolled in the health promotion program Living with Style and Health, between October 2011 and June 2016, at the Paulista University health clinics (Sao Paulo). Data collection was performed during the first appointment of the program using an instrument based on the form used in the VIGITEL system of the Ministry of Health. Only questions related to eating habits, physical activity level, smoking and alcohol consumption were selected. Participants had several risk factors for chronic diseases: family history for diabetes (50%) and hypertension (62.3%); overweight (38.5%) and obesity (25%); abdominal circumference above normal parameters (61.3%); low level of recommended physical activity (37%); and low recommended consumption of fruits and vegetables (8.8%). Men differed from women in relation to higher alcohol consumption (p=0.02), higher food intake with excess fat (p=0.01), and lower level of physical activity in the displacement (p≤0.05). It is suggested to encourage the training of health professionals to understand the determinants of health risk behaviors, so that they can interfere with them.